Cuidados paliativos y calidad de vida de los pacientes de la casa de enfermos terminales de la Fundación Liga de Caridad Lojana de la ciudad de Loja, durante el periodo febrero - julio del 2015 - Estrella Lima, Adriana Elizabeth (2016)
This project aimed to determine the impact that Palliative Care has on the quality of life of patients at the local Hospice for the Terminally Ill (HTI) run by the Charity League Foundation of Loja (CLFL). To achieve the overall aim, the following objectives were set: to specify what palliative care was offered to patients at the HTI, to evaluate the patients' quality of life and relate it to the palliative care they received, and to develop a proposed protocol in order to improve the management of suitable palliative care given to this group of patients. This transversal analytical-qualitative-quantitative research took place at the HTI run by the CLFL, it included 24 patients who were admitted to and resided in the HTI between February and July 2015. For each patient, the study applied a data collection card, a symptom control evaluation sheet, nutritional screening MNA (Mini nutritional assessment), Katz index and Goldberg anxiety and depression scales. By means of the aforementioned methods it was determined that the palliative care provided to the patients at the HTI consisted of: neurological symptoms treatment for 54.17% of the patient population; digestive symptoms 50%; pain, respiratory symptoms, skin symptoms, anorexia and cachexia 41.67%; 87.5% are bathed daily, 83.3% are fed with meals cooked at the center, 70.83% received supportive therapy; and 50% of patients had family support. In the process of assessing the quality of life, it was possible to conclude that most of the patients who presented symptoms and were treated, had their symptoms under control. However, 29.17% presented neurological symptoms that were not able to be controlled; which was the same for 25% of the population who reported pain, anorexia and cachexia despite having received treatment for the symptoms. The other evaluated standards showed that 50% of patients presented malnutrition, 83.33% had adequate hygiene; 87.5% displayed severe disability; and 70.83% likely suffer from anxiety; while 62.5% showed a probable depression. Given the aforementioned issues, a protocol for improving palliative care was developed, which will allow for a more appropriate medical participation to improve the quality of life until death. KEYWORDS: Palliative care, quality of life, terminal illness, hospice for the terminally ill, symptom control.